"دور التجارة الإلكترونية في الحد من خسائر المؤسسات الاقتصادية خلال الازمات ""ازمة كوفيد 19 انموذجا- " - انيس, باي; علاء الدين, ولابي; احمد ياسين, دركي (University of eloued جامعة الوادي, 2021)
"التّجارة الدوليّة من أهمّ مُقوّمات نجاح وازدهار الاقتصاد لكافة دول العالم؛ حيث تظهر أهميتها في دورها الذي يدعم استفادة كلّ دولة من المميّزات التي تُقدمها الدول الأُخرى؛ بسبب عدم قُدرة الدول على توفير درجات مجتمعاتها بالاعتماد على مواردها المحليّة، كما من الممكن الاستفادة من هذه الموارد في حال استخدامها بطُرقٍ جيّدة؛ بهدف تصديرها لدول العالم. يعود ضهور التجارة الإلكترونية إلى ثلاثة عقود مضت من القرن الماضي، تعتمد هذه التجارة على نظام معلوماتي أدواته كلها إلكترونية تتمثل في الحاسب الآلي وملحقاته كشبكة الأنترنت، الهاتف والفاكس والتلكس إلى غيرها من التقنيات التي تلعب دورا مؤثرا في نشاط التجارة حتى سداد مقابل الوفاء في هذه التجارة فإنه يتم بطريقة إليكترونية وذلك عن طريق التحويلات الإلكترونية للنقود أو التسوق بطاقات الدفع والإئتمان وتشمل التجارة الإلكترونية كل المعاملات التجارية، من بيع وشراء للسلع والخدمات وقد إعتبرها المحللين الإقتصاديين بأنها محرك جديد للتنمية الإقتصادية وذلك كونها وسيلة فعالة وسريعة لإبرام الصفقات والمنتجات والخدمات وترويجها. حيث تقوم إدارة التجارة الالكترونية بالتنسيق بين التطبيقات والبنى التحتية والدعامات. ""International trade is one of the most important ingredients for the success and prosperity of the economy of all countries of the world; Where its importance appears in its role that supports the benefit of each country from the advantages offered by other countries; Due to the inability of countries to provide the scores of their societies by relying on their local resources, it is also possible to benefit from these resources if they are used in good ways; With the aim of exporting it to countries around the world. The emergence of electronic commerce dates back to three decades of the last century. This commerce depends on an information system whose tools are all electronic represented in the computer and its accessories such as the Internet, telephone, fax and telex to other technologies that play an influential role in trade activity until payment for fulfillment in this trade It is done electronically through electronic transfers of money or shopping, payment and credit cards. E-commerce includes all commercial transactions, from buying and selling goods and services. Economic analysts have considered it as a new engine for economic development, as it is an effective and fast way to conclude deals, products and services and promote them. The E-Commerce Department coordinates between applications, infrastructures, and supports."
مذكرة ماستر تسويق سياحي
Keywords: التجارة الالكترونية - كوفيد19 - تكنولوجيا المعلومات- المؤسسات الاقتصادية.; E-commerce - COVID-19 - Information technology - Economic institutions.